The use of relaxometry to evaluate the aging process in hybrid HIPS nanocomposites. (December 2015) - da Silva, Paulo Sergio Rangel Cruz; Tavares, Maria Inês Bruno
Abstract: Nuclear magnetic resonance allows measurement of proton spin-lattice relaxation times, which reflect the molecular mobility of the sample according to the changes in its chemical structure caused by different mechanisms that can be induced. Nanomaterials and their derivatives are good systems to investigate through NMR relaxometry due to their particular organization and intermolecular interaction. In this study, NMR relaxometry was employed to evaluate UV aging of HIPS nanomaterials formed by the solution method. The results obtained were quite interesting. Regardless of organoclay amount, the aging effect occurred slowly up to 200 h of UV light exposure. However, at 300 h of UV light exposure, competition between chain degradation and chain recombination occurred, and at 400 h the aging effect increased the chain scission.